Antibiogram and stress response to salmonella infection in Philippine native chickens - Balala, Lotis M.; Mendoza, Bernadette C.; Baldrias, Loinda R.; Parungao-Balolong, Marilen; Masangkay, Joseph S. (2022)
Free-range native chicken production is beset by multiple environmental threats. This study aimed to detect Salmonella from environmental samples and cloacal swabs of Philippine native chickens, characterize antimicrobial resistance pattern, and assess stress response to infection. Salmonella was detected through culture and PCR assay. The disk diffusion method was used to describe resistance pattern and differential leukocyte count to assess stress response. The overall detection rate of Salmonella was 8.9% (21/237), 2.11% (5/237), and 8.04% (16/199) of which were detected by culture and PCR, respectively. Isolates were 80% susceptible to amoxicillin-clavulanic acid and 60% to norfloxacin, cefaclor, and chloramphenicol. An intermediate to susceptible pattern (40%-80%) was demonstrated to ciprofloxacin, norfloxacin, and gentamicin. Antibiotic resistance was 80% in ampicillin, doxycycline, tetracycline, and trimethoprim-sulfamethoxazole; 60% in kanamycin and cefuroxime; and 40% in neomycin. Multidrug resistance was demonstrated by 80% of the isolates which had MAR indices ranging from 0.43-0.57. The H:L ratio was significantly high (p-value=0.005) during the highest detection rate at Day 150 indicating a stressful state. The study suggests the potential of native chickens as reservoir for multidrug-resistant Salmonella they possibly acquire from the environment. Attention should be given to the environmental conditions to which native chickens are raised.
Keywords: Resistance to antibiotics; Salmonella; Chickens